THE INFLUENCE OF SOCIAL MEDIA ON ONLINE POLITICAL PARTICIPATION OF NOVICE VOTERS ON THE ISLAND OF JAVA AHEAD OF THE 2024 ELECTION - Bianti, Sabila Riska; Bakry, Gema Nusantara (Jurnal Politik Pemerintahan Dharma Praja, 2024)
Community political participation is a very necessary involvement in the General Election process. Every Indonesian citizen who already has the right to vote is certainly required to participate in voicing his or her voice in the election. According to several studies, there is an influence of media exposure on the level of political participation. Therefore, this study aims to explore more deeply the influence of social media exposure on the online political participation of novice voters in Java ahead of the 2024 General Election. This research uses a quantitative descriptive method, with data collection techniques using questionnaires distributed through social media as primary data in the time span from November 27, 2023 to December 6, 2023. The population used is the community of novice voters on the island of Java with a sample taken as many as 395 people from the calculation of the convenience sampling technique. In analyzing this research data, simple linear regression analysis techniques were used. The results of this research show that there is an influence of exposure to social media on the online political participation of novice voters on the island of Java ahead of the 2024 elections.